Efficacy and safety of nintedanib in patients with systemic sclerosis-associated interstitial lung disease treated with mycophenolate: a subgroup analysis of the SENSCIS trial. Issue 1 (January 2021) - Highland, Kristin B; Distler, Oliver; Kuwana, Masataka; Allanore, Yannick; Assassi, Shervin; Azuma, Arata; Bourdin, Arnaud; Denton, Christopher P; Distler, Jörg H W; Hoffmann-Vold, Anna Maria; Khanna, Dinesh; Mayes, Maureen D; et al.
Summary: Background: In the Safety and Efficacy of Nintedanib in Systemic Sclerosis (SENSCIS) trial, nintedanib reduced the rate of decline in forced vital capacity (FVC) in patients with systemic sclerosis-associated interstitial lung disease (SSc-ILD). Patients on stable treatment with mycophenolate for at least 6 months before randomisation could participate. The aim of this subgroup analysis was to examine the efficacy and safety of nintedanib by mycophenolate use at baseline. Methods: The SENSCIS trial was a randomised, double-blind, placebo-controlled trial, in which patients with SSc-ILD were randomly assigned (1:1) to receive 150 mg of oral nintedanib twice daily or placebo for at least 52 weeks. In a prespecified subgroup analysis, we analysed the primary endpoint of rate of decline in FVC over 52 weeks by mycophenolate use at baseline. In a post-hoc analysis, we analysed the proportion of patients with an absolute decrease in FVC of at least 3·3% predicted at week 52 (proposed minimal clinically important difference estimate for worsening of FVC in patients with SSc-ILD) in subgroups by mycophenolate use at baseline. Adverse events were reported in subgroups by mycophenolate use at baseline. Analyses were done in all participants who received at least one dose of study drug. We analysed the annual rate of decline in FVC using a random coefficient regression model (with random slopes and intercepts) including anti-topoisomerase I antibody status, age, height, sex, and baseline FVC as covariates and terms for baseline-by-time, treatment-by-subgroup, and treatment-by-subgroup-by-time interactions. SENSCIS is registered with ClinicalTrials.gov, NCT02597933, and is now complete. Findings: Between Nov 30, 2015, and Oct 31, 2017, 819 participants were screened and 576 were enrolled, randomly assigned to, and treated with nintedanib (n=288) or placebo (n=288). 139 (48%) of 288 in the nintedanib group and 140 (49%) of 288 in the placebo group were taking mycophenolate at baseline. In patients taking mycophenolate at baseline, the adjusted mean annual rate of decline in FVC was –40·2 mL per year (SE 19·8) with nintedanib and –66·5 mL per year (19·3) with placebo (difference: 26·3 mL per year [95% CI –27·9 to 80·6]). In patients not taking mycophenolate at baseline, the adjusted mean annual rate of decline in FVC was –63·9 mL per year (SE 19·3) with nintedanib and –119·3 mL per year (19·0) with placebo (difference: 55·4 mL per year [95% CI 2·3 to 108·5]). We found no heterogeneity in the effect of nintedanib versus placebo on the annual rate of decline in FVC between the subgroups by mycophenolate use (p value for interaction=0·45). In a post-hoc analysis, the proportion of patients with an absolute decrease in FVC of at least 3·3% predicted was lower with nintedanib than with placebo in both patients taking mycophenolate (40 [29%] of 138 vs 56 [40%] of 140; odds ratio 0·61 [0·37 to 1·01]) and those not taking mycophenolate (59 [40%] of 149 vs 70 [47%] of 148; 0·73 [0·46 to 1·16]) at baseline. The adverse event profile of nintedanib was similar between the subgroups. Diarrhoea, the most common adverse event, was reported in 106 (76%) of 139 patients in the nintedanib group and 48 (34%) of 140 in the placebo group among those taking mycophenolate at baseline, and in 112 (75%) of 149 in the nintedanib group and 43 (29%) of 148 in the placebo group among those not taking mycophenolate at baseline. Over the entire trial period, 19 patients died (ten in the nintedanib group and nine in the placebo group). One death in the nintedanib group was considered to be related to study drug. Interpretation: Nintedanib reduced the progression of interstitial lung disease both in patients with SSc-ILD who were and were not using mycophenolate at baseline, with no heterogeneity in its treatment effect detected between the subgroups. The adverse event profile of nintedanib was similar in the subgroups by mycophenolate use. Our findings suggest that the combination of mycophenolate and nintedanib offers a safe treatment option for patients with SSc-ILD. More data are needed on the benefits of initial combination therapy versus a sequential approach to treatment of SSc-ILD. Funding: Boehringer Ingelheim.